Analisis Risiko IT untuk Pemanfaatan Tools Genogram pada Health care - sukmadiningtyas, sukmadiningtyas; Fathoni, M Yoka (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
This research analysis the genogram tool uses to record a person's health history as a medium for supporting health. This research analyzes the risks that might occur in a polyclinic if a genogram tool is implemented. The analysis process is through a risk identification process then a risk assessment using the COBIT for Risk IT method as IT resource mapping, then qualitative analysis as a method of mapping possibilities and impacts according to FGDs with organizations which can be used as a guide in assessing risks. level. Meanwhile, bow tie analysis is a risk mapping method that allows risk recovery so that it can serve as a guide for recovery. The results of risk analysis using the Genogram tool show several conditions, namely low probability but high level of impact, low probability but medium impact, and high probability of impact.